Robust reference gene selection in Norway spruce: essential for real-time quantitative PCR across different tissue, stress and developmental conditions - Singh, Vivek Vikram; Naseer, Aisha; Sellamuthu, Gothandapani; Mogilicherla, Kanakachari; Gebauer, Roman; Roy, Amit; Jakuš, Rastislav (Frontiers in Forests and Global Change, 2024)
Accurate gene expression analysis in Norway spruce (Picea abies) under diverse stress conditions requires the identification of stable reference genes for normalization. Notably, the literature lacks reports on suitable reference genes in Norway spruce. Here, we aimed to address this gap by identifying suitable reference genes for quantitative real-time PCR in Norway spruce across various stress conditions (drought, heat, pathogen infection) in seedlings, tissues (needle, phloem, root), and developmental stages (seedlings, mature trees). We evaluated the stability of 15 candidate reference genes and assessed their expression stability using five statistical algorithms (ΔCt, geNorm, NormFinder, BestKeeper, and RefFinder). Our results highlight ubiquitin-protein ligase (SP1), conserved oligomeric Golgi complex (COG7), and tubby-like F-box protein (TULP6) as the most stable reference genes, while succinate dehydrogenase (SDH5) and heat shock protein 90 (HSP90) were the least stable under various experimental conditions. COG7 and TULP6 are novel candidate reference genes reported for the first time. The expression stability of the identified reference genes was further validated using dehydrin-like protein 5 (PaDhn5) under drought conditions in Norway spruce. Pairwise variation analysis suggests that two reference genes were sufficient to normalize gene expression across all sample sets. This study provides a comprehensive analysis of reference gene stability under different experimental conditions and a catalog of genes for each condition, facilitating future functional genomic research in Norway spruce and related conifers.